Experiences of Hispanic Families with Social Services in the Racially Segregated Southeast: Views from Administrators and Workers in North Carolina - Barnes, Carolyn Y. (Race and social problems, 2021)
North Carolina—as a state in the racially segregated Southeast—offers a unique context to understand access to social services for Hispanic families and children. Theories of administrative burden posit that Hispanic families likely face high learning, compliance, and psychological costs. Hispanic families face challenges that compound these costs: limited English language and literacy proficiency, complex household composition, and citizenship status of family members and other household members. With new survey results and qualitative data on social service administrators and front-line workers, we examine how these costs may affect access to programs for Hispanic families who reside in a state with a history of racial divisions that have shaped local policy implementation. Some workers noted transportation barriers and complex application processes as limiting access. While we expected to find that Hispanic families may be disadvantaged by decentralized service delivery in a manner that is similar to the experiences of African American families, workers instead note significant resources that help facilitate Hispanic families’ access to programs. Workers view national anti-immigrant policies and rhetoric, rather than state and local policy rules or resource constraints, as limiting their capacity to serve Hispanic families.